Consumer behavior of women towards purchasing decision on passenger cars - V.J., DR. MAHESH; KUMAR, DILIP . (The journal of contemporary issues in business and government, 2020)
The present study focuses on the purchasing behaviour of women towards cars. The study examines the factors which influence women buyers while purchasing a car. Women are prone to various factors while purchasing any automobile, such as driving comfort, performance, after sales service, opinion from their friends, parents, partner, and colleagues. The survey has been conducted in analyzing women consumers preferences on purchasing a car. Data collected among 100 women respondents from different fields. This study attempts to understand the buying decision process of women individually or in group. The main aim of the study examines the preferences of women while purchasing a car. This survey will be helpful for the automobile industry and others who like to study the purchasing behaviour of women consumers.